2019
DOI: 10.1007/s00213-019-5188-5
|View full text |Cite
|
Sign up to set email alerts
|

Altered glutamatergic response and functional connectivity in treatment resistant schizophrenia: the effect of riluzole and therapeutic implications

Abstract: Rationale Anterior cingulate cortex (ACC) glutamatergic abnormalities are reported in treatment-resistant schizophrenia (TRS) and implicated in functional dysconnectivity and psychopathology. Preclinical evidence indicates riluzole reduces synaptic glutamate. However, it is unknown whether riluzole can modulate glutamate metabolite levels and associated functional connectivity in TRS. Objectives To examine the relationship between glutamatergic function and cortical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 58 publications
0
43
2
Order By: Relevance
“…Riluzole (2‐amino‐6‐trifluormethoxy benzothiazole) has also been shown to reduce synaptic glutamate levels through a wide range of mechanisms, and an initial trial found it to be effective in treating negative symptoms in schizophrenia, potentially by altering striatocortical connectivity. Similarly, lamotrigine inhibits glutamate release via inhibition of several ion channels, and attenuates the psychotomimetic effects of ketamine.…”
Section: Treatmentmentioning
confidence: 99%
“…Riluzole (2‐amino‐6‐trifluormethoxy benzothiazole) has also been shown to reduce synaptic glutamate levels through a wide range of mechanisms, and an initial trial found it to be effective in treating negative symptoms in schizophrenia, potentially by altering striatocortical connectivity. Similarly, lamotrigine inhibits glutamate release via inhibition of several ion channels, and attenuates the psychotomimetic effects of ketamine.…”
Section: Treatmentmentioning
confidence: 99%
“…A further relevant compound is the glutamate-release inhibitor riluzole ( de Boer et al, 2019 ) [although see ( da Silva et al, 2003 )]. Riluzole was effective in decreasing glutamate/glutamine (Glx) levels in anterior cingulate cortex (hippocampus was not reported) in treatment-resistant patients with schizophrenia, in whom Glx-levels also correlated with negative and cognitive symptoms ( Pillinger et al, 2019 ). Furthermore, riluzole-treatment was effective in reducing negative symptoms in patients with schizophrenia in a small-scale clinical trial ( Farokhnia et al, 2014 ).…”
Section: Targeting Hippocampal Hyperactivity Pharmacologicallymentioning
confidence: 99%
“…Interestingly, the drug of choice for treating TRS patients is the atypical antipsychotic clozapine (which also acts on serotonin pathways), as these patients usually are not responsive to treatment with typical antipsychotics (which mainly act on dopamine pathways) 27 , 28 . Studies have indicated that TRS may be particularly linked to aberrant neurodevelopment, as impaired cortical and striatal functional connectivity was observed in TRS 28 30 . In addition, we have also reported significant differences in NDEL1 enzyme activity between antipsychotic naïve first-episode psychosis (FEP) patients compared to HCs after treatment with risperidone, with a progressive decrease in NDEL1 activity observed during 2 months and/or 1 year of treatment with (atypical antipsychotic) risperidone, during which a significant improvement of symptoms was observed in all patients, with significant positive correlation observed between NDEL1 activity decrease and these symptoms amelioration, as assessed by PANSS 31 .…”
Section: Introductionmentioning
confidence: 99%